Dynamic study of N ` N-dimethylparanitroaniline encapsulated in silicalite-1 matrix using neutron spin-echo spectroscopy - Bhange, Deu S.; Dejoie, C.; Porcher, F.; Malikova, N.; Martinetto, P.; Dooryhee, E.; Anne, M. (European Physical Journal-Special Topics, 2010)
The present work focuses on the dynamic studies of N'N-dimethyl-paranitroaniline (dmpNA) encapsulated in silicalite zeolite. Quasielastic neutron scattering (QENS) experiments are carried out using neutron spin-echo technique. Polarisation of the scattered neutron beam is measured at carefully chosen values of Q = 0.35, 0.9, 1.1 and 1.45 angstrom(-1) at fixed T = 298K and at fixed Q = 0.9 angstrom(-1) at 150, 200, 250 and 298 K. This gives insight into the motion and the related activation energy of the guest dmpNA molecule. The quasielastic signal observed in the present system within the time range considered is due to fast local rotational motions of protons of the end methyl groups. The results are in good agreement with the dynamics of methyl group rotations reported in the literature by back-scattering QENS technique.